572 Work-related asthma associated with high prevalence of respiratory symptoms and reduced work-ability in a cross-sectional population based study from norway. (24th April 2018) - Klepaker, G; Svendsen, MV; Kongerud, J; Fell, AKM
Abstract : Introduction: Some studies have indicated that patients with occupational asthma have more severe disease than other asthma patient. Indicators of severity may be reduced quality of life and higher levels of sick-leave and disability. There are, however, few studies assessing respiratory symptom prevalence and work-ability. The aim of our study was to estimate the differences in respiratory symptom prevalence and work-ability between patients with indication of work-related asthma compared with other asthma patients. Methods: The association between work-relation and respiratory symptoms and work ability was assed among 16 099 subjects from the general population, aged 16 to 50 years, included in a cross-sectional study form Telemark, Norway. 828 subjects that reported having physician-diagnosed asthma, ever being employed and currently using asthma medication were included. Of these 171 (21%) had respiratory symptoms at work that improved during weekends, holydays, other absence from work or change of work. These were compared with the remaining patients with physician-diagnosed asthma (n=657). Self-reported work-ability was assessed by the first single item question of the work ability index (WAI). Analyses where adjusted for age, gender, education and occupational group. Result: The patients with work-related asthma reported significantly more respiratory symptoms in the past 12 months; wheezing (OR 2.6, 95% CI: 1.5 to 4.5), woken by dyspnoea during the night (OR 2.0, 95% CI: 1.4 to 2.8), woken by coughing (OR 1.8, 95% CI: 1.3 to 2.6), asthma attack (OR 2.2, 95% CI: 1.5 to 3.1) and reduced work-ability (OR 2.3, 95% CI: 1.5 to 3.3). Discussion: Our study indicates that work-related asthma is associated with higher prevalence of respiratory symptoms and reduced work-ability (score <8) compared with asthma without work-relation. These findings support the hypothesis suggesting that occupational asthma may be more severe than non-occupational asthma.